Surface Quality and Long-term Dimensional Stability of Current Elastomeric Impression Materials after Disinfection - Mary P. Walker, DDS, PhD;1 Meagan Rondeau, BS;2 Cynthia Petrie, DDS, MS;3 (Journal of Prosthodontics, 2007)
The objectives of this investigation were to evaluate the effect of disinfection on surface quality and dimensional stability of more recent, reformulated vinylpolysiloxane (VPS) and polyether (PE) materials.